Islamic Index With an Islamic Economic Approach to the Judgment Strategy in the Concept of Working Capital and Income During the Covid 19 Pandemic - Arnida Wahyuni Lubis; Andri Soemitra (Lembaga Riset Ilmiah, 2022)
This study looks at the current economic conditions that have an impact on the company. The author wants to provide the variables of Alms Fund and ISR Fund Allocation in company activities. With the hope that it will provide opportunities for the company to be able to improve the company. The Zakat Fund, which means the greater the funds spent and the allocation of funds for ICSR, gives a good image for the company. Because the company can channel the funds, it means that the company does not suffer a loss. So that it will attract sympathetic investors to invest in the company. The purpose of this study is to describe the literature on the Islamic Index with an Islamic Economic Approach to the Effect of Judgment Strategy in the Concept of Working Capital and Income During the Covid 19 Pandemic in Islamic accounting for five years, 2017-2022. The research method used in this research is qualitative research with content analysis of papers from the Google Scholar database. Researchers found 154 papers, after going through a selection process, the author finally reviewed 17 articles that were considered the most relevant